Trust, Regulation and Market Failures - Pinotti, Paolo (The Review of Economics and Statistics, 2012)
Government regulation of firms is associated with more negative externalities and unofficial activity across countries. I argue that this correlation mainly reflects causality going from concerns about market failures to demand for government intervention. Using trust in others as a proxy for such concerns, I show that differences in trust explain a great deal of variation in entry regulations. Then, controlling for trust in the regression of market failures on regulation, the latter is no longer associated with worse economic outcomes. The same result is confirmed when I exploit country population as an alternative source of variation in regulation.